The Effects of Remittances on Poverty and Inequality Alleviation in Selected Central and South-East European Countries - Tashevska, Biljana; Mamuchevska, Daniela; Merdzan, Gjunter (Faculty of Economics and Business, University of Belgrade, 2022)
In recent decades, the countries from Central and South-Eastern Europe (CESEE) have experienced sizeable emigration, accompanied by growing remittance inflows. In some countries, especially developing countries, remittances present a significant source of foreign exchange inflow and of income for poorer families. However, empirical research on the impact of remittances on poverty and inequality has yielded mixed results. Most studies find that remittances help alleviate poverty, while the impact on inequality is more ambiguous. This paper empirically examines the impact of remittances on poverty and inequality in 16 countries from the CESEE region. Using the Generalized Method of Moments, we evaluate two specific panel regression models for the impact of remittances on poverty and income inequalities in this group of countries, accounting for the different levels of economic development and different macroeconomic and institutional settings. In addition, the paper also examines whether different institutional quality impacts poverty and inequality. The paper's preliminary results indicate that remittances reduce poverty and inequality in the analyzed countries, and that better institutional quality further improves the obtained results. The results of this paper could have significant implications for policymakers. Given that institutions appear to be important in the way remittances are used and for the benefits that they provide, the best way for governments to ensure that remittances play a role in reducing poverty and income inequality is to foster better institutional quality.
Book of Abstracts
Keywords: Remittances, Poverty, Inequality, CESEE countries